(untitled) (Scientific journal of the Fergana State University, 2024)
The article presents information about the insects found in the pea agrobiocenoses of the Northern Fergana. The collected samples showed that 10 species belonging to 6 families and 7 genera are found in the pea agrobiocenosis of Northern Fergana. The continental climatic conditions of Northern Fergana have a significant impact on the distribution and life cycle of the scaly insects in the area.